APPLICATION OF HYPERSPHERICAL COORDINATES TO 4-ATOM REACTIVE SCATTERING - H-2+CN-]H+HCN - Brooks, A; Clary, D (1990)
We develop the use of Delves' hyperspherical coordinates to study the reactive scattering of four-atom systems within the collinear approximation. We present quantum mechanical calculations of reaction probabilities for the collinear exothermic reaction H2 + CN →H+HCN. We use a potential energy surface which reproduces the essential characteristics of the reaction. The effect of freezing the CN bondlength to its equilibrium value during the reaction is also investigated and is found to be a good approximation. It is found that HCN product vibrational states with the C-H stretch excited are produced preferentially in the reaction. © 1990 American Institute of Physics.